1991
DOI: 10.1111/j.1471-6402.1991.tb00479.x
|View full text |Cite
|
Sign up to set email alerts
|

The Hairless Ideal: Women and Their Body Hair

Abstract: A major component of “femininity” in the United States today is a hairless body, a norm that developed in the United States between 1915–1945. Little has been written regarding the development of this norm, and virtually no empirical research has been done to assess how universally ascribed to is this standard or why women actually remove their leg and underarm hair. More than 200 women from two national professional organizations responded to a mailed questionnaire (response rate 56%). The majority (around 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
95
3
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(109 citation statements)
references
References 4 publications
8
95
3
3
Order By: Relevance
“…The only two published social psychological surveys on women's hair removal strongly support this hypothesis: Basow (1991) found that 81% of the professional North American women in her sample reported removing their leg and/or underarm hair; and Tiggemann and Kenyon (1998) found that 91.5% of their Australian university student sample removed their leg hair, and 93% removed their underarm hair. Tiggemann and Kenyon also surveyed a group of Australian high school students, and found similar results: 92% reported removing their leg hair, and 91.2% their underarm hair.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…The only two published social psychological surveys on women's hair removal strongly support this hypothesis: Basow (1991) found that 81% of the professional North American women in her sample reported removing their leg and/or underarm hair; and Tiggemann and Kenyon (1998) found that 91.5% of their Australian university student sample removed their leg hair, and 93% removed their underarm hair. Tiggemann and Kenyon also surveyed a group of Australian high school students, and found similar results: 92% reported removing their leg hair, and 91.2% their underarm hair.…”
mentioning
confidence: 82%
“…Hair removal, then, may well be "[s]tatistically ...one of the most frequent ways women alter their bodies to achieve the ideal of youthfulness and attractiveness" (Tiggemann & Kenyon, 1998, p. 874). As such, women's depilatory practices not only contribute substantially to the cosmetic industry, but reinforce the view that underpins all the body-changing procedures, from make-up application to cosmetic surgery: that a woman's body is unacceptable if left unaltered (see Basow, 1991;Chapkis, 1986;Tiggemann & Kenyon, 1998).…”
mentioning
confidence: 99%
See 3 more Smart Citations